Respuesta :
Answer:
$61.80
Explanation:
The proportion can be written ...
... total cost/price = $25.75/$25.00 = item cost/$60.00
Multiplying by $60, we get ...
... item cost = $60.00×25.75/25 = $60.00×1.03
... item cost = $61.80
Answer:
Total cost = $61.8
Step-by-step explanation:
We know that the total cost of an item (including the sales tax) is directly proportional to its price so we can write is as:
Total cost ∝ price
To change this proportionality into an equality, we need a constant so it will be:
Total cost = k * price
Finding k when total cost is $25.75 and price is $25:
25.75 = k * 25
k = 1.03
Finding the total cost when price $60:
Total cost = 1.03 * 60
Total cost = $61.8